Heat Stress Tolerance in Rice (Oryza sativa L.): Identification of Quantitative Trait Loci and Candidate Genes for Seedling Growth Under Heat Stress - Kilasi, Newton Lwiyiso; Singh, Jugpreet; Vallejos, Carlos Eduardo; Ye, Changrong; Jagadish, S. V. Krishna; Kusolwa, Paul; Rathinasabapathi, Bala (Frontiers in Plant Science, 2018)
Productivity of rice, world’s most important cereal is threatened by high temperature stress, intensified by climate change. Development of heat stress-tolerant varieties is one of the best strategies to maintain its productivity. However, heat stress tolerance is a multigenic trait and the candidate genes are poorly known. Therefore, we aimed to identify quantitative trait loci (QTL) for vegetative stage tolerance to heat stress in rice and the corresponding candidate genes. We used genotyping-by-sequencing to generate single nucleotide polymorphic (SNP) markers and genotype 150 F8 recombinant inbred lines obtained by crossing heat tolerant ‘N22’ and heat susceptible ‘IR64’ varieties. A linkage map was constructed using 4074 high quality SNP markers that corresponded to 1638 recombinationally unique events in this mapping population. Seven QTL for root length and two for shoot length under control conditions with 2.1% to 12% effect were identified. One QTL rlht5.1 was identified for ‘root length under heat stress’ with 20.4% effect. Four QTL were identified for ‘root length under heat stress as percent of control’ that explained the total phenotypic variation from 5.2% to 8.6%. Three QTL with 5.3% to 10.2% effect were identified for ‘shoot length under heat stress’ and seven QTL with 6.6% to 19% effect were identified for ‘shoot length under heat stress expressed as percentage of control’. Among the QTL identified six were overlapping between those identified using shoot traits and root traits and two were overlapping between QTL identified for ‘shoot length under heat stress’ and ‘shoot length expressed as percentage of control’. Genes coding 1037 potential transcripts were identified based on their location in 10 QTL regions for vegetative stage heat stress tolerance. Among these, 213 transcript annotations were reported to be connected to stress tolerance in previous research in the literature. These putative candidate genes included transcription factors, chaperone proteins (e.g. alpha-crystallin family heat shock protein 20 and DNAJ homolog heat shock protein), proteases, protein kinases, phospholipases and proteins related to disease resistance and defense and several novel proteins currently annotated as expressed and hypothetical proteins.